Fragile X Mutations and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A posiible link between predisposition for epilepsy and mutations in the fragile X mental retardation-1 gene (FMR) was investigated in the Neuropediatric Department, Behandlungszentrum Vogtareuth; and Laboratory of Genetic Diagnostics, Munchen, Germany.